A contribution to the modelling of human induced excitation on pedestrian bridges. (May 2017) - Casciati, Fabio; Casciati, Sara; Faravelli, Lucia
Highlights: A time variant stochastic field models the forces from the walking of persons. A realization from the model is simulated as excitation for a wood footbridge. The case study considers different idealizations of the human induced excitation. The responses obtained from these models are compared to actual records. Abstract: Human induced vibration is a common problem in the design of planking levels as both flooring or decking. The source of the vibration is the so-called "human induced loading (HIL)". Models are available for a single exciting person and for a dense aggregation of persons. Small groups of persons should also be considered in view of serviceability limit state design. This paper introduces a model for the time variant stochastic fields of forces induced by the walking of a small group of persons. A numerical example is presented dealing with the evaluation of vertical and transversal accelerations at nodes of a finite element model of an existing wood footbridge. The example considers different idealizations of the human induced excitation and the results of these models are compared to actual records.